Tooth desensitizing cationic material, its manufacturing method and its application
A cationic hydrogel formed by bonding polymers with cationic groups effectively addresses the limitations of current dentin hypersensitivity treatments by providing long-lasting desensitization with high efficacy.
Patent Information
- Application Number
- JP2024560805
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-06-29
- Filing Date
- 2022-09-05
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Current treatments for dentin hypersensitivity are time-consuming and have limited therapeutic effects, with effectiveness rates ranging from 15.7% to 85.2% and often requiring complex procedures.
A cationic material formed by covalently bonding a main chain skeleton polymer, such as polysaccharides or synthetic polymers, with cationic groups like primary amino groups, is used to create a tooth desensitizing hydrogel that can penetrate dentinal tubules, reducing sensitivity through cation migration.
The cationic hydrogel demonstrates a desensitization effectiveness of over 85-95% in clinical trials, lasting for 3 months without significant decrease, and is easier to apply than existing methods, causing no damage to teeth.
Smart Images

Figure 2024545936000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an oral cavity material, a method for producing the same, and applications thereof, and more particularly to a cationic material with tooth desensitizing effect, a method for producing the same, and applications thereof. [Background technology]
[0002] Dentin hypersensitivity is a condition in which exposed dentin experiences short, sharp pain due to external stimuli, resulting in tooth defects or lesions with no identifiable cause. Typical stimuli include temperature, wind, mechanical, or chemical stimuli. At present, the most widely accepted mechanism of dentin hypersensitivity is the fluid dynamics theory. In other words, when dentin is exposed, various external temperature changes, mechanical stimuli, or chemical stimuli act on the surface of the exposed dentinal tubules, causing the flow of the fluid in the dentinal tubules to change, increasing the amount of fluid or changing its direction, and this abnormal flow is transmitted to the dental pulp, exciting the nerves and causing pain.
[0003] Currently, the treatments for dentin hypersensitivity mainly include toothpastes for hypersensitivity containing various ingredients, desensitizing mouthwashes containing fluoride, desensitizing drugs such as resin adhesives and fluoride coatings, gluma desensitizing agents, and lasers for desensitization treatment. According to the cited literature, the various desensitization methods currently used clinically have different effects, and when using toothpastes for hypersensitivity, the effectiveness rate is 15.7-31.1% immediately and 54.9-85.2% after 3 months; when using laser sealing, the effectiveness rate is 88.7-94% immediately and 58-83% after 3 months; when using resin adhesives, the effectiveness rate is 62.3-73% immediately and 65-77% after 3 months.
[0004] Furthermore, the treatment of dentin hypersensitivity with the above substances is more complicated and time-consuming, while the effectiveness of the treatment is limited, and in clinical practice, patients still experience some degree of dentin hypersensitivity symptoms. Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention provides a cationic material with a high desensitizing effect, a method for producing the same, and applications thereof, in order to solve the problems that the treatment of dentin hypersensitivity using materials in the prior art takes time and has limited effectiveness. [Means for solving the problem]
[0006] Therefore, the present invention provides a tooth desensitizing cationic material comprising a main chain skeletal polymer and a cationic group derived therefrom bound by a covalent bond, wherein the main chain skeletal polymer is any combination of one or more of polysaccharides, synthetic polymers or proteins, and the cationic group is any combination of one or more of primary amino groups, primary amine salts, secondary amino groups, secondary amine salts, tertiary amino groups, tertiary amine salts, quaternary amino groups, quaternary amine salts, piperidinium, pyrrolidine, imidazolinium and pyridinium.
[0007] Preferably, the polysaccharides include one or more of hydroxyethyl cellulose, hydroxypropyl cellulose, carboxymethyl cellulose, hyaluronic acid, chitosan, alginate, lignin, dextran, soluble starch, polysaccharides; the synthetic polymers include one or more of polyethylene glycol, branched polyethylene glycol, polyvinyl alcohol, polyoxyethylene polyoxypropylene ether block copolymer, dimethyl diallyl ammonium chloride, carbomer, poly(meth)acrylic acid esters, poly(meth)acrylamides, polyethyleneimine, polyamino acids; and the proteins include one or more of gelatin, collagen, elastin, elastin-like polypeptides, fibroin, serum albumin, casein, soy protein, mucin, fibrin, polynucleotides.
[0008] Preferably, the tooth desensitizing cationic material is a hydrogel solution containing 0.1% by mass to 10% by mass of polyquaternium-10 having a molecular weight of 100 to 5000 kDa, a charge density of 0.0001 to 0.002 eq / g, and a nitrogen content of 0.5 to 2.5 wt %.
[0009] The present invention relates to a method for producing a polysaccharide, a polysaccharide, a polyvinyl alcohol, a polyoxyethylene polyoxypropylene ether block copolymer, a polysaccharide, a polyvinyl alcohol, a poly(meth)acrylic acid ester, a poly(meth)acrylamide, a polyethylenimine, a polyamino acid, a gelatin, a collagen, an elastin, an elastin-like polypeptide, a fibroin, a serum albumin, a casein, a soy protein, a mucin, a fibrin, and a polynucleotide. in deionized water, stirring until uniformly dissolved, and then adding a combined solution of a modifier having one or more groups selected from the group consisting of a primary amino group, a primary amine salt, a secondary amino group, a secondary amine salt, a tertiary amino group, a tertiary amine salt, a quaternary amino group, a quaternary amine salt, piperidinium, pyrrolidine, imidazolinium, and pyridinium, and sodium hydroxide to react with each other; (2) neutralizing the reaction mixture of step (1) with hydrochloric acid until it becomes neutral, and then dialyzing and freeze-drying the mixture to obtain a cationic material; and (3) using the cationic material obtained in step (2) to prepare a 0.1% by mass to 10% by mass cationic material hydrogel solution.
[0010] Preferably, in the step (1), the reaction is carried out at 30 to 95°C with stirring for 0.5 to 24 hours; in the step (3), the cationic material is slowly added to deionized water with rapid stirring, and the temperature is raised to 30 to 95°C in order to accelerate the swelling rate of the cationic material, and after 0.5 to 24 hours, a cationic hydrogel solution is prepared as a uniform and transparent solution.
[0011] The present invention also provides use of a cationic tooth desensitizing material for producing a medicament for treating dentin hypersensitivity.
[0012] Preferably, in the use of the tooth desensitizing cationic material for producing a therapeutic agent for dentin hypersensitivity provided by the present invention, the tooth desensitizing cationic material is used to produce a cationic hydrogel material at a concentration of 0.01% by mass to 10% by mass.
[0013] Preferably, in the use of the tooth desensitizing cationic material for producing a medicament for treating dentin hypersensitivity provided by the present invention, the tooth desensitizing cationic material is used to produce a dentifrice.
[0014] Preferably, in the use of the tooth desensitizing cationic material provided by the present invention for producing a dentin hypersensitivity treatment drug, the tooth desensitizing cationic material is applied to the surface of a dental cap, and finally, a backside film layer is attached to the cationic gel.
[0015] Preferably, in the use of the tooth desensitizing cationic material for manufacturing a dentin hypersensitivity treatment drug provided by the present invention, the tooth surface covering includes a bracket, a tooth gel, a mouthpiece, a pack, and a chewing gum; and the back film layer is one or more of an EVA film, a PLA film, and a PVA film. Effect of the Invention
[0016] The present invention has the following advantages. The cationic tooth desensitizing material provided by the present invention can effectively penetrate into dentinal tubules. Tests have demonstrated that the cationic tooth desensitizing material provided by the present invention clearly reduces the current value caused by acidic stimulation, alkaline stimulation, cold stimulation, hot stimulation, and pressure stimulation, and the action potential in an animal dentin hypersensitivity model. In addition, clinical desensitization experiments have shown that the cationic tooth desensitizing material can effectively reduce the pain of patients, with the therapeutic efficacy rate being 85-95% or more in each case, and no obvious decrease in efficacy was observed after three months of observation, with the efficacy rate still remaining at 85-90%. Compared with desensitization methods such as toothpastes for treating hypersensitivity, resin adhesives, fluorides, and lasers that are currently widely used clinically, the cationic desensitizing material of the present invention has the advantages of simple clinical operation, sustained therapeutic effect, and no damage to the affected tooth or the patient. [Brief description of the drawings]
[0017] [Figure 1A] FIG. 1A is a synthesis reaction scheme for polyquaternium-10, which is the main component of the tooth desensitizing cationic material of the present invention. [Figure 1B] FIG. 1B is a synthesis reaction scheme of CSMA hydrogel, which is the main component of the tooth desensitizing cationic material of the present invention. [Diagram 2] Figures 2A and 2B are images of dentinal tubules treated with positive and negative staining solutions in the present invention, photographed with a confocal laser microscope, with Figure 2A showing dentinal tubules treated with a positive staining solution and Figure 2B showing dentinal tubules treated with a negative staining solution. [Diagram 3] Figures 3A, 3B, and 3C are schematic diagrams of the penetration of a sulforhodamine-stained cationic hydrogel (polyquaternium-10 hydrogel) into dentinal tubules observed using a confocal laser microscope in the present invention, with Figure 3A being a schematic diagram of the penetration of the cationic hydrogel into the tubules observed from the sagittal plane, Figure 3B being a schematic diagram of the penetration of the cationic hydrogel into the tubules observed from the frontal plane, and Figure 3C being a schematic diagram of the cationic hydrogel filling the dentinal tubules and blocking cation migration due to stimulation. [Figure 4] FIG. 4 is a schematic diagram showing the construction of a dentin hypersensitivity model of the present invention. [Figure 5A] Figures 5A, 5B, and 5C show the results of electrochemical testing of a dentin hypersensitivity model of an extracted tooth treated with PQ-10 hydrogel, where Figure 5A is a schematic diagram of the reaction current measured upon acid and alkali stimulation. [Figure 5B] FIG. 5B is a schematic diagram of the reaction current measured in response to a temperature stimulus. [Figure 5C] FIG. 5C is a schematic diagram of the reaction current measured by pressure stimulation. [Figure 5D] 5D, 5E, and 5F show the results of electrochemical testing of a dentin hypersensitivity model of a living animal treated with PQ-10 hydrogel, with FIG. 5D being a schematic diagram of the reaction current measured upon acid and alkali stimulation. [Figure 5E] FIG. 5E is a schematic diagram of the reaction current measured in response to a temperature stimulus. [Figure 5F] FIG. 5F is a schematic diagram of the response current measured by pressure stimulation. [Figure 6A] Figures 6A, 6B, and 6C show the results of electrochemical testing of a dentin hypersensitivity model of an extracted tooth treated with CSMA hydrogel, where Figure 6A is a schematic diagram of the reaction current measured upon acid and alkali stimulation. [Figure 6B] FIG. 6B is a schematic diagram of the reaction current measured in response to a temperature stimulus. [Figure 6C] FIG. 6C is a schematic diagram of the reaction current measured by pressure stimulation. [Figure 6D] Figures 6D, 6E, and 6F show the results of electrochemical testing of a dentin hypersensitivity model in a living animal treated with CSMA hydrogel, with Figure 6D being a schematic diagram of the reaction current measured upon acid and alkali stimulation. [Figure 6E] FIG. 6E is a schematic diagram of the reaction current measured in response to a temperature stimulus. [Figure 6F] FIG. 6F is a schematic diagram of the response current measured by pressure stimulation. [Figure 7] FIG. 7 shows the results of electrophysiological measurements of a dentin hypersensitivity model in a living animal. [Figure 8A]FIG. 8A shows the results of a clinical desensitization experiment of a cationic hydrogel (polyquaternium-10 hydrogel). [Figure 8B] FIG. 8B shows the results of a clinical desensitization experiment of a cationic hydrogel (methacryloylated chitosan hydrogel). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The present invention will now be further described with reference to examples.
[0019] Example 1 Characterization of the charging properties inside the dentinal tubules: 5 mg of positively charged rhodamine-6g powder was dissolved in 1 ml of deionized water, placed in a thermostatic shaker at 25 °C, and operated at 300 r / min for 5 min in the dark to ensure sufficient dissolution, to prepare a rhodamine-6g staining solution. The dentin portion of the extracted tooth was sliced horizontally to a thickness of about 1 mm, and an acid etchant containing 30% phosphoric acid was applied to the dentin slice for 30 s, and the acid etchant was washed with water for 15 s to remove the surface stain layer. The treated dentin slice was applied with rhodamine-6g staining solution, left for 30 min in the dark, and then washed with deionized water 5 times every 1 min until the color of the washing solution disappeared, and the slice was observed with a confocal laser microscope. As a result, as shown in Figure 2A, staining was observed inside the dentinal tubules, and the staining gradually weakened from the end close to the dental pulp to the end far from the dental pulp. The staining results showed that the inside of the dentinal tubules was negatively charged, with a tendency to gradually weaken from the end closest to the dental pulp to the end furthest from it. Similarly, 5 mg of negatively charged sulforhodamine powder was dissolved in 1 ml of deionized water, placed in a thermostatic shaker at 25°C, and operated at 300 rpm for 5 minutes in the dark to ensure sufficient dissolution, to prepare a sulforhodamine staining solution. When dentinal tubule slices were treated with the sulforhodamine staining solution and observed with a confocal laser microscope, no staining was observed inside the dentinal tubules, as shown in Figure 2B, indicating that the inside of the dentinal tubules was an asymmetrically distributed negatively charged environment.
[0020] Example 2 The present invention provides a cationic hydrogel that is a 3% by weight polyquaternium-10 hydrogel. 30 mg of polyquaternium-10 powder (molecular weight 450 kDa, charge density 0.0012 eq / g, nitrogen content 1.85 wt%) was weighed out and slowly added to 1 mL of deionized water with rapid stirring, and the temperature was raised to 65°C to accelerate the swelling rate of polyquaternium-10. After 1 hour, a 3% by weight polyquaternium-10 hydrogel solution was prepared as a homogeneous and transparent solution. This sample was sterilized in an autoclave at 120°C for 30 minutes and stored in a refrigerator at 4°C.
[0021] Example 3 The present invention provides a cationic hydrogel that is a 0.1% by mass polyquaternium-10 hydrogel solution. 10 mg of polyquaternium-10 powder (molecular weight 100 kDa, charge density 0.002 eq / g, nitrogen content 2.5 wt%) was weighed out and slowly added to 1 mL of fast-stirring phosphate salt buffer (molar concentration 50 mM, pH 8), and the temperature was raised to 30°C to accelerate the swelling rate of polyquaternium-10. After 0.5 hours, a 0.1% by mass polyquaternium-10 hydrogel solution was prepared as a uniform and transparent solution. This sample was sterilized in an autoclave at 120°C for 30 minutes and stored in a refrigerator at 4°C.
[0022] Example 4 The present invention provides a cationic hydrogel that is a 10% by weight polyquaternium-10 hydrogel solution. 50 mg of polyquaternium-10 powder (molecular weight 2000 kDa, charge density 0.0010 eq / g, nitrogen content 1.5 wt%) was weighed out and slowly added to 1 mL of citrate buffer solution (molar concentration 200 mM, pH 5) that was being stirred rapidly, and the temperature was raised to 75°C to accelerate the swelling rate of polyquaternium-10. After 5 hours, a 10% by weight polyquaternium-10 hydrogel solution was prepared as a uniform and transparent solution. The sample was sterilized in an autoclave at 120°C for 30 minutes and stored in a refrigerator at 4°C.
[0023] The results showed that the 0.1% cationic hydrogel had a weak effect on the results of the current and action potential induced by stimulation when applied, but the 3% cationic hydrogel produced good results on the current and action potential induced by stimulation when applied.Furthermore, in vitro and in vivo experimental verification of the treatment of dentin hypersensitivity was performed using the 3% cationic hydrogel.
[0024] Example 5 The present invention provides a method for producing a cationic hydrogel, comprising the steps of: (1) dispersing hydroxyethyl cellulose in deionized water, stirring until uniformly dissolved, and then adding and reacting sodium hydroxide and 2,3-epoxypropyltrimethylammonium chloride solutions, respectively; (2) neutralizing the reaction mixture of the step (1) with hydrochloric acid until it becomes neutral, and then dialyzing and freeze-drying the mixture to obtain cationized hydroxyethyl cellulose, i.e., polyquaternium-10; and (3) using the polyquaternium-10 obtained in the step (2) to prepare a 3% by mass polyquaternium-10 hydrogel solution.
[0025] In the step (1), the mixture is stirred at 65° C. for 24 hours. In the step (2), the polyquaternium-10 has a molecular weight of 450 kDa, a charge density of 0.0012 eq / g, and a nitrogen content of 1.85 wt%. In the step (3), the polyquaternium-10 is slowly added to deionized water under fast stirring, and the temperature is raised to 65° C. to accelerate the swelling rate of the polyquaternium-10. After 1 hour, a polyquaternium-10 hydrogel solution is prepared as a uniform and transparent solution.
[0026] Example 6 This is a cationic desensitizing hydrogel, which is a desensitizing agent that blocks cationic migration in dentinal tubules by cations and treats dentin hypersensitivity. We will verify the therapeutic effect of the cationic hydrogel by producing a hydrogel desensitizing agent using methacryloyl chitosan (synthesis of chitosan modified by methacrylic anhydride; CSMA).
[0027] The CSMA hydrogel used in the present invention is prepared as follows. The CSMA conjugate is synthesized by one-step N-acetylation reaction with chemical selectivity between chitosan and methacrylic anhydride, and its chemical formula is shown in FIG. 2B. That is, methacrylic anhydride was added dropwise to a 1 wt.% chitosan solution in acetic acid so that the ratio of acid anhydride to amino group was 1:1. After reacting at 60°C and stirring for about 6 hours, the reaction solution was dialyzed in distilled water for about 3 days in the dark (molecular weight cutoff of dialysis bag MW 3500 Da), freeze-dried, and the final sponge-like product was obtained and stored at room temperature. Method of use: Prepare a 10% by weight hydrogel using CSMA material, apply the desensitizing hydrogel to the exposed dentin surface of the affected tooth, and wipe off the excess hydrogel after 5 minutes to achieve the desensitizing therapeutic effect.
[0028] Example 7 A cationic desensitizing hydrogel and its manufacturing method. Hydroxypropyl cellulose was dispersed in deionized water and stirred until it was uniformly dissolved. The required amount of sodium hydroxide and 2,3-epoxypropyltrimethylammonium chloride solution were added, and the mixture was reacted for 24 hours with stirring at 65°C. Finally, the reaction mixture was neutralized with hydrochloric acid until it was neutral, dialyzed in deionized water for 3 days in a 10 kDa dialysis bag, freeze-dried, and weighed to obtain cationized hydroxypropyl cellulose. 30 mg of cationized hydroxypropyl cellulose powder was weighed out and slowly added to 1 mL of deionized water with rapid stirring, and the temperature was raised to 65°C to accelerate the swelling rate. After 1 hour, a 3% by mass hydrogel solution was prepared as a uniform and transparent solution. The sample was sterilized in an autoclave at 120°C for 30 minutes and stored in a refrigerator at 4°C.
[0029] Example 8 A cationic desensitizing hydrogel and its manufacturing method. Hydroxypropyl cellulose was dispersed in deionized water and stirred until it was uniformly dissolved. The required amounts of sodium hydroxide and 2,3-epoxypropyldimethylamine solution were added and reacted for 24 hours with stirring at 65°C. Finally, the reaction mixture was neutralized with hydrochloric acid until it was neutral, dialyzed in deionized water for 3 days in a 10 kDa dialysis bag, freeze-dried and weighed to obtain cationized hydroxypropyl cellulose. 30 mg of cationized hydroxypropyl cellulose was weighed out and slowly added to 1 mL of deionized water with rapid stirring, and the temperature was raised to 65°C to accelerate the swelling rate. After 1 hour, a 3% by mass hydrogel solution was prepared as a uniform and transparent solution. The sample was sterilized in an autoclave at 120°C for 30 minutes and stored in a refrigerator at 4°C.
[0030] Example 9 A cationic desensitizing hydrogel and its manufacturing method. Hydroxypropyl cellulose was dispersed in deionized water and stirred until it was uniformly dissolved. The required amounts of sodium hydroxide and 1-epoxypropyl-3-methylimidazole chloride solution were added, and the mixture was reacted for 24 hours with stirring at 65°C. Finally, the reaction mixture was neutralized with hydrochloric acid until it was neutral, dialyzed in deionized water for 3 days in a 10 kDa dialysis bag, freeze-dried, and weighed to obtain cationized hydroxypropyl cellulose. 30 mg of cationized hydroxypropyl cellulose powder was weighed out and slowly added to 1 mL of deionized water that was being stirred rapidly, and the temperature was raised to 65°C to accelerate the swelling rate. After 1 hour, a 3% by mass hydrogel solution was prepared as a uniform and transparent solution. The sample was sterilized in an autoclave at 120°C for 30 minutes and stored in a refrigerator at 4°C.
[0031] Example 10 A cationic desensitizing hydrogel and its manufacturing method. Polyvinyl alcohol was dispersed in deionized water and stirred until it was uniformly dissolved. The required amount of sodium hydroxide and 2,3-epoxypropyltrimethylammonium chloride solution were added, and the mixture was reacted for 24 hours while stirring at 65°C. Finally, the reaction mixture was neutralized with hydrochloric acid until it was neutral, dialyzed in deionized water for 3 days using a 10 kDa dialysis bag, freeze-dried, and weighed to obtain a cationic polyvinyl alcohol. 100 mg of cationic polyvinyl alcohol powder was weighed out and slowly added to 1 mL of deionized water that was being stirred rapidly, and the temperature was raised to 65°C to accelerate the swelling rate. After 1 hour, a 10% by mass hydrogel solution was prepared as a uniform and transparent solution. The sample was sterilized in an autoclave at 120°C for 30 minutes and stored in a refrigerator at 4°C.
[0032] Example 11 A cationic desensitizing hydrogel and its manufacturing method. Polyvinyl alcohol was dispersed in deionized water and stirred until it was uniformly dissolved. The required amounts of sodium hydroxide and 2,3-epoxypropyldimethylamine solution were added and reacted for 24 hours while stirring at 65°C. Finally, the reaction mixture was neutralized with hydrochloric acid until it was neutral, dialyzed in deionized water for 3 days in a 10 kDa dialysis bag, freeze-dried and weighed to obtain a cationic polyvinyl alcohol. 100 mg of cationic polyvinyl alcohol powder was weighed out and slowly added to 1 mL of deionized water with rapid stirring, and the temperature was raised to 65°C to accelerate the swelling rate. After 1 hour, a 10% by mass hydrogel solution was prepared as a uniform and transparent solution. The sample was sterilized in an autoclave at 120°C for 30 minutes and stored in a refrigerator at 4°C.
[0033] Example 12 A cationic desensitizing hydrogel and its manufacturing method. Polyvinyl alcohol was dispersed in deionized water and stirred until it was uniformly dissolved. The required amount of sodium hydroxide and 1-epoxypropyl-3-methylimidazole chloride solution were added, and the mixture was reacted for 24 hours while stirring at 65°C. Finally, the reaction mixture was neutralized with hydrochloric acid until it was neutral, dialyzed in deionized water for 3 days using a 10 kDa dialysis bag, freeze-dried, and weighed to obtain a cationic polyvinyl alcohol. 100 mg of cationic polyvinyl alcohol powder was weighed out and slowly added to 1 mL of deionized water that was being stirred rapidly, and the temperature was raised to 65°C to accelerate the swelling rate. After 1 hour, a 10% by mass hydrogel solution was prepared as a uniform and transparent solution. The sample was sterilized in an autoclave at 120°C for 30 minutes and stored in a refrigerator at 4°C.
[0034] Example 13 A cationic desensitizing hydrogel and its manufacturing method. Gelatin was dispersed in deionized water and stirred until it was uniformly dissolved. The required amount of sodium hydroxide and 2,3-epoxypropyltrimethylammonium chloride solution were added, and the mixture was reacted for 24 hours with stirring at 65°C. Finally, the reaction mixture was neutralized with hydrochloric acid until it was neutral, dialyzed in deionized water for 3 days in a 10 kDa dialysis bag, freeze-dried, and weighed to obtain cationized gelatin. 50 mg of cationized gelatin powder was weighed out and slowly added to 1 mL of deionized water with rapid stirring, and the temperature was raised to 65°C to accelerate the swelling rate. After 1 hour, a 5% by mass hydrogel solution was prepared as a uniform and transparent solution. The sample was sterilized in an autoclave at 120°C for 30 minutes and stored in a refrigerator at 4°C.
[0035] Example 14 A cationic desensitizing hydrogel and its manufacturing method. Gelatin was dispersed in deionized water and stirred until it was uniformly dissolved. The required amounts of sodium hydroxide and 2,3-epoxypropyldimethylamine solution were added and reacted for 24 hours with stirring at 65°C. Finally, the reaction mixture was neutralized with hydrochloric acid until it was neutral, dialyzed in deionized water for 3 days in a 10 kDa dialysis bag, freeze-dried and weighed to obtain cationized gelatin. 50 mg of cationized gelatin powder was weighed out and slowly added to 1 mL of deionized water with rapid stirring, and the temperature was raised to 65°C to accelerate the swelling rate. After 1 hour, a 5% by mass hydrogel solution was prepared as a uniform and transparent solution. This sample was sterilized in an autoclave at 120°C for 30 minutes and stored in a refrigerator at 4°C.
[0036] Example 15 A cationic desensitizing hydrogel and its manufacturing method. Gelatin was dispersed in deionized water and stirred until it was uniformly dissolved. The required amounts of sodium hydroxide and 1-epoxypropyl-3-methylimidazole chloride solution were added, and the mixture was reacted for 24 hours with stirring at 65°C. Finally, the reaction mixture was neutralized with hydrochloric acid until it was neutral, dialyzed in deionized water for 3 days in a 10 kDa dialysis bag, freeze-dried, and weighed to obtain cationized gelatin. 50 mg of cationized gelatin powder was weighed out and slowly added to 1 mL of deionized water with rapid stirring, and the temperature was raised to 65°C to accelerate the swelling rate. After 1 hour, a 5% by mass hydrogel solution was prepared as a uniform and transparent solution. The sample was sterilized in an autoclave at 120°C for 30 minutes and stored in a refrigerator at 4°C.
[0037] Example 16 This is a cationic desensitizing dentifrice that blocks cationic migration in dentinal tubules by cations and treats dentin hypersensitivity. The cationic material obtained above and the dentifrice base material are mixed uniformly at a mass ratio of 1: (10-1000), where the base material contains a friction agent (25-60%), a humectant, an adhesive, a foaming agent, a sweetener (0.01-0.1%), a certain volume of deionized water, a preservative and a flavoring. The flavoring, active additive, stabilizer and saccharin are uniformly dissolved in a preliminary dissolving pot or a preliminary mixing pot and placed in a paste manufacturing pot, and the liquid materials in the liquid material storage tank are weighed and placed in the paste manufacturing pot, and the powder material is further added. After the powder material is added, the flavoring is further added, and blade stirring, homogeneous stirring and polishing are performed. The mixture is driven into a paste storage pot and aged, naturally cooled to room temperature, and expanded sufficiently to form a uniform adhesive body, thereby increasing the elasticity of the material. The aging time was about 120 minutes. How to use: When brushing your teeth, apply a small amount of toothpaste to the exposed dentin of the sensitive affected tooth, then wipe off the toothpaste after 10 minutes to achieve the desensitization treatment effect.
[0038] Example 17 This is a cationic desensitizing bracket that uses cations to block cation migration in dentinal tubules and treat dentin hypersensitivity. The cationic hydrogel obtained above was applied to the mucosal surface of the bracket at a thickness of 100 μm, and the hydrogel application layer was covered with a film (PVA film) on the back side of the mucosal surface to obtain a dentin-sensitive desensitizing agent that blocks cation migration in dentinal tubules using cations. How to use: Peel off the back film (PVA film) of the bracket, place the bracket in your mouth, and place the mucosal surface with cationic gel in contact with the exposed dentin of the sensitive affected tooth. After one hour, the desensitization treatment effect will be achieved.
[0039] Example 18 This is a cationic desensitizing toothpaste gel that is a desensitizing agent that uses cations to block cation migration in dentinal tubules and treat dentin hypersensitivity. The cationic material obtained above was applied to the surface of the toothpaste gel in a thickness of 300 μm, and the hydrogel coating layer was covered with a back film (PLA film) to obtain a dentin sensitive desensitizing agent that uses cations to block cation migration in dentinal tubules. How to use: Peel off the back film (PLA film) of the toothpaste gel, contact the cationic gel with the exposed dentin surface of the sensitive affected tooth, and after 2 hours, the desensitization treatment effect will be achieved.
[0040] Example 19 This is a cation desensitizing mouthpiece that is a desensitizing agent that uses cations to block cation migration in dentinal tubules and treat dentin hypersensitivity. The above-obtained cation gel was applied to the surface of the mouthpiece in a thickness of 500 μm, and the hydrogel coating layer was covered with a back film (EVA film) to obtain a dentin-sensitive desensitizing agent that uses cations to block cation migration in dentinal tubules. How to use: Peel off the back film (EVA film) of the mouthpiece, contact the cationic gel with the exposed dentin surface of the sensitive affected tooth, and after 3 hours, the desensitization treatment effect will be achieved.
[0041] Example 20 This is a cationic desensitizing pack that uses cations to block cation migration in dentinal tubules and treat dentin hypersensitivity. The cationic gel obtained above was applied to the mucosal surface of the pack at a thickness of 10 μm, and the hydrogel coating layer was covered with a back film (PLA film) to obtain a dentin-sensitive desensitizing agent that uses cations to block cation migration in dentin tubules. How to use: Peel off the back film (PLA film) of the pack, contact the cationic gel with the exposed dentin surface of the sensitive affected tooth, and after 2 hours, the desensitization treatment effect will be achieved.
[0042] Example 21 The ingress effect of cationic materials into dentinal tubules is detected, and the ingress of cationic materials into dentinal tubules is detected using the PQ-10 cationic hydrogel and CSMA cationic hydrogel prepared in Example 2 and Example 3. 5 mg of negatively charged sulforhodamine powder was dissolved in 1 mL of gel, placed in a thermostatic shaker at 25°C, and operated at 300 r / min for 5 minutes in the dark to fully dissolve. The dentin part of the extracted tooth was sliced horizontally to a thickness of about 1 mm, and an acid etchant containing 30% phosphoric acid was applied to the dentin slice for 30 seconds, and the acid etchant was washed with water for 15 seconds to remove the surface dirt layer. The treated dentin slice was applied with a dyed cationic hydrogel, left to stand for 5 minutes in the dark, and then observed with a confocal laser microscope. As shown in Figure 3, the dyed cationic hydrogel effectively entered the dentinal tubules in the visible range. A schematic diagram is shown in Figure 3C.
[0043] Example 22 The desensitizing effect of the cationic materials, PQ-10 cationic hydrogel and CSMA cationic hydrogel prepared in Example 2 and Example 3, in a dentin hypersensitivity model of an extracted tooth was detected by an electrochemical detection method.
[0044] 1) A dentin hypersensitivity model was constructed on an extracted tooth, and the positive electrode of the picoammeter measurement electrode was placed in the electrolytic cell, and the negative electrode in the dental pulp cavity. Under an external voltage of 0 V, pressure stimuli (100, 200, 300, 400 mmHg), acid / alkalinity stimuli (pH 5, 5.5, 6, 6.5, 7.5, 8, 8.5, 9), and cold / hot stimuli (5, 13, 21, 29, 45, 53, 61, 69°C) were applied to the electrolyte solution (physiological saline solution) in the electrolytic cell, and the current change in the dentin hypersensitivity model was detected. 2) In the dentin hypersensitivity model of extracted teeth, the maximum forward current value due to acid stimulation was approximately 43.06 nA, but after gel treatment the forward current value decreased to 22.67 nA. The maximum reverse current value due to alkaline stimulation was approximately -19.53 nA, but after PQ-10 gel treatment the reverse current value decreased to -11.05 nA. 3) In the dentin hypersensitivity model of extracted teeth, the maximum forward current value due to cold stimulation was approximately 475.4nA, but the forward current value after gel treatment was approximately 207.25nA. The maximum reverse current value due to heat stimulation was approximately -425.2nA, but the reverse current value after PQ-10 gel treatment decreased to -218.55nA. 4) In the dentin hypersensitivity model of extracted teeth, the forward current value due to maximum pressure stimulation was approximately 28.36 nA, but after PQ-10 gel treatment, the forward current value decreased to 22.18 nA.
[0045] The results of treatment of extracted teeth with PQ-10 gel are shown in Figures 5A, 5B, and 5C. When treated with CSMA hydrogel, the results were similar to those of the PQ-10 gel, and are shown in Figures 6A, 6B, and 6C.
[0046] Example 23 The desensitizing effect of the cationic materials, PQ-10 cationic hydrogel and CSMA cationic hydrogel prepared in Example 2 and Example 3, in a dentin hypersensitivity model of a living animal was detected by electrochemical detection method.
[0047] 1) A dentin hypersensitivity model was constructed in the mandibular molar of a piglet, an experimental animal, and the positive electrode of the picoammeter measurement electrode was placed in the electrolytic cell, and the negative electrode in the dental pulp cavity. Under an external voltage of 0 V, pressure stimuli (100, 200, 300, 400 mmHg), acid / alkalinity stimuli (pH 5, 5.5, 6, 6.5, 7.5, 8, 8.5, 9), and cold / heat stimuli (5, 13, 21, 29, 45, 53, 61, 69℃) were applied to the electrolyte solution (physiological saline solution) in the electrolytic cell, and the current change of the dentin hypersensitivity model was detected. 2) In an animal model of dentin hypersensitivity, the maximum forward current value induced by acid stimulation was approximately 55.49 nA, but after gel treatment, the forward current value decreased to 30.48 nA. The maximum reverse current value induced by alkaline stimulation was approximately -33.15 nA, but after PQ-10 gel treatment, the reverse current value decreased to approximately -15.72 nA. 3) In an animal model of dentin hypersensitivity, the maximum forward current value induced by cold stimulation was approximately 556 nA, but after gel treatment the forward current value was approximately 238.74 nA. The maximum reverse current value induced by heat stimulation was approximately -551.32 nA, but after PQ-10 gel treatment the reverse current value decreased to -235.42 nA. 4) In an animal model of dentin hypersensitivity, the forward current value induced by maximum pressure stimulation was approximately 44.26 nA, but after PQ-10 gel treatment, the forward current value decreased to 25.84 nA.
[0048] The results of extracted tooth treatment with PQ-10 gel are shown in Figures 5D, 5E, and 5F. When treated with CSMA hydrogel, the results were similar to those of the PQ-10 gel, and are shown in Figures 6D, 6E, and 6F.
[0049] Example 24 The desensitizing effect of the cationic materials, PQ-10 cationic hydrogel and CSMA cationic hydrogel prepared in Example 2 and Example 3, in a dentin hypersensitivity model of a living animal was detected by electrophysiological detection method.
[0050] 1) In a dentin hypersensitivity model of a living animal, the mandibular nerve trunk that controls sensation of the mandibular molars was separated by dissection and separated by about 2 cm, and the measurement electrodes of the electrophysiological measurement device were attached to the mandibular nerve trunk. When various stimuli were applied to the dentin hypersensitivity model, changes in the action potential of the mandibular nerve trunk were detected. 2) The amplitude of the action potential induced by acid stimulation was about 0.4 mV, but after gel treatment, the amplitude of the action potential decreased to about 0.15 mV. The amplitude of the action potential induced by alkaline stimulation was about 0.3 mV, but after gel treatment, the amplitude of the action potential decreased to about 0.1 mV. 3) The amplitude of the action potential induced by cold stimulation was about 0.7 mV, but after gel treatment, the amplitude of the action potential decreased to about 0.3 mV. The amplitude of the action potential induced by heat stimulation was about 0.5 mV, but after gel treatment, the amplitude of the action potential decreased to about 0.2 mV. 4) The amplitude of the action potential induced by pressure stimulation was approximately 0.3 mV, but after gel treatment the amplitude of the action potential decreased to 0.15 mV.
[0051] The effect of desensitization treatment as determined by electrophysiological detection is shown in FIG.
[0052] Example 25 Application of clinical desensitization test: The PQ-10 cationic hydrogel and CSMA cationic hydrogel prepared in Example 2 and Example 3 were used to detect the desensitization effect of cationic materials in clinical trials.
[0053] The VAS scores of 20 patients with dentin hypersensitivity were compared before and after treatment with PQ-10 hydrogel or CSMA hydrogel, and in a second examination 3 months after treatment. The cationic hydrogel was found to have a high desensitization effect and a long duration of effect.
[0054] The results of the desensitization therapeutic effect of the PQ-10 hydrogel are shown in FIG. 8A, and the results of the desensitization therapeutic effect of the CSMA hydrogel are shown in FIG. 8B.
[0055] Although the above is a description, it is only a specific embodiment of the present invention and is not intended to limit the scope of the present invention. Therefore, any equivalent replacement of the configuration, or any modification or amendment based on the description of the claims of the present invention, will naturally be understood to fall within the scope of the claims of the present invention.
Claims
1. A cationic material having a tooth desensitizing effect, which comprises a main chain skeleton polymer and a cationic group derived therefrom, bound by a covalent bond, The main chain skeleton polymer is one or more of polysaccharides, synthetic polymers, or proteins, in any combination; The cationic group is one or any combination of a primary amino group, a primary amine salt, a secondary amino group, a secondary amine salt, a tertiary amino group, a tertiary amine salt, a quaternary amino group, a quaternary amine salt, piperidinium, pyrrolidine, imidazolinium, and pyridinium.
2. the polysaccharides include one or more of hydroxyethyl cellulose, hydroxypropyl cellulose, carboxymethyl cellulose, hyaluronic acid, chitosan, alginate, lignin, dextran, soluble starch, polysaccharides; The synthetic polymers include one or more of polyethylene glycol, branched polyethylene glycol, polyvinyl alcohol, polyoxyethylene polyoxypropylene ether block copolymer, dimethyldiallylammonium chloride, carbomer, poly(meth)acrylic acid esters, poly(meth)acrylamides, polyethyleneimine, and polyamino acids; The tooth desensitizing cationic material according to claim 1, characterized in that the proteins include one or more of gelatin, collagen, elastin, elastin-like polypeptides, fibroin, serum albumin, casein, soy protein, mucin, fibrin, and polynucleotides.
3. The tooth desensitizing cationic material according to claim 1, characterized in that it is a hydrogel solution containing 0.1% by mass to 10% by mass of polyquaternium-10 having a molecular weight of 100 to 5000 kDa, a charge density of 0.0001 to 0.002 eq / g, and a nitrogen content of 0.5 to 2.5 wt %.
4. (1) Hydroxyethyl cellulose, hydroxypropyl cellulose, carboxymethyl cellulose, hyaluronic acid, alginate, lignin, dextran, soluble starch, polysaccharides, polyethylene glycol, branched polyethylene glycol, polyvinyl alcohol, polyoxyethylene polyoxypropylene ether block copolymer, dimethyl diallyl ammonium chloride, carbomer, poly(meth)acrylic acid esters, poly(meth)acrylamides, polyethyleneimine, polyamino acids, gelatin, collagen, elastin, a step of dispersing any combination of one or more of elastin-like polypeptides, fibroin, serum albumin, casein, soy protein, mucin, fibrin, and polynucleotides in deionized water, stirring until uniformly dissolved, and then adding a combined solution of a denaturant having one or more groups selected from a primary amino group, a primary amine salt, a secondary amino group, a secondary amine salt, a tertiary amino group, a tertiary amine salt, a quaternary amino group, a quaternary amine salt, piperidinium, pyrrolidine, imidazolinium, and pyridinium, and sodium hydroxide to react with each other; (2) neutralizing the reaction mixture of step (1) with hydrochloric acid until neutral, and then dialyzing and lyophilizing the mixture to obtain a cationic material; (3) A method for producing a cationic material with tooth desensitizing effect, comprising the step of preparing a 0.1% by mass to 10% by mass cationic material hydrogel solution using the cationic material obtained in the step (2).
5. In the step (1), the mixture is stirred at 30 to 95° C. for 0.5 to 24 hours. The method for producing a cationic material with tooth desensitization effect according to claim 4, characterized in that in step (3), the cationic material is slowly added to deionized water under fast stirring, the temperature is raised to 30-95°C to accelerate the swelling speed of the cationic material, and after 0.5-24 hours, a cationic hydrogel solution is prepared as a homogeneous and transparent solution.
6. 2. Use of the cationic tooth desensitizing material according to claim 1 for the manufacture of a medicament for treating dentin hypersensitivity.
7. 7. The use according to claim 6, characterized in that the cationic hydrogel material is present in an amount of 0.01% to 10% by weight.
8. 7. The use according to claim 6, characterized in that said cationic tooth desensitizing material is used to prepare a dentifrice.
9. 7. The method according to claim 6, characterized in that the cationic tooth desensitizing material is applied to the surface of a dental veneer and finally a backing film layer is applied to the cationic gel.
10. The tooth surface covering includes a bracket, a toothpaste gel, a mouthpiece, a pack, and a chewing gum. The use according to claim 9, characterized in that the backside film layer is one or more of the following: EVA film, PLA film, PVA film.
Citation Information
Patent Citations
High molecular desensitisation paste and preparation method thereof
CN110755297A
Oral and tooth care and cleaning agents with improved antibacterial effect II
EP2476406A2
Composition for relaxing and removing dental pain supersensitivity
JP1994065083A
Use of quaternary ammonium alkyl hydroxyethyl cellulose ethers as hair conditioners and skin conditioners
JP2004519519A
Cellulose ether
JP2006527785A
